CAR-T therapy: pioneering a new era in the treatment of autoimmune diseases - Wu, Yuanhao; Han, Luyao; Wang, Yu; Gu, Mengjiao; Wang, Yunuo; Gao, Jingyue; Huang, Hanjing; Li, Chen (Frontiers in Immunology, 2025)
CAR-T therapy, an innovative immunotherapeutic approach, genetically modifies T cells to express CARs, enabling targeted destruction of specific antigen-expressing cells. Initially developed for oncology, CAR-T therapy has shown significant potential in treating autoimmune diseases. By targeting CD19+ B cells, CAR-T therapy has demonstrated rapid and sustained remission in refractory cases, with studies showing normalized laboratory parameters and reduced disease activity. At the same time, CAR-NK, CAAR-T and CAR-Treg technologies further broaden therapeutic strategies. However, some adverse effects also exist, including CRS, ICANS and so on. Despite these challenges, CAR therapy represents a promising advancement in autoimmune disease treatment, with ongoing research aimed at enhancing efficacy, durability, and safety. Continuous innovation is essential to address limitations and optimize therapeutic outcomes.